2024
DOI: 10.1371/journal.pone.0294289
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning in public health: Comparative predictive models for COVID-19 case forecasting

Muhammad Usman Tariq,
Shuhaida Binti Ismail

Abstract: The COVID-19 pandemic has had a significant impact on both the United Arab Emirates (UAE) and Malaysia, emphasizing the importance of developing accurate and reliable forecasting mechanisms to guide public health responses and policies. In this study, we compared several cutting-edge deep learning models, including Long Short-Term Memory (LSTM), bidirectional LSTM, Convolutional Neural Networks (CNN), hybrid CNN-LSTM, Multilayer Perceptron’s, and Recurrent Neural Networks (RNN), to project COVID-19 cases in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 152 publications
0
1
0
Order By: Relevance
“…It can be seen that four of the models have competitively outperformed the original UAE paper [28], with an improvement of over 30%. A more recent work published in 2024 [43] also tests multiple deep learning models for forecasting COVID-19 in the UAE and Malaysia. The authors reported an MAE of 0.046 and an R 2 score of 0.004 for their Univariate LSTM model.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that four of the models have competitively outperformed the original UAE paper [28], with an improvement of over 30%. A more recent work published in 2024 [43] also tests multiple deep learning models for forecasting COVID-19 in the UAE and Malaysia. The authors reported an MAE of 0.046 and an R 2 score of 0.004 for their Univariate LSTM model.…”
Section: Discussionmentioning
confidence: 99%